CLASSIFICATION, CALCULATION METHODS, AND DIRECTIONS FOR TECHNICAL IMPROVEMENT OF GAS-LUBRICATED BEARINGS - Breshev, Oleksii; Nosko, Pavlo; Bashta, Oleksandr; Radko, Oleg; Bohdan, Svitlana; Herasymova, Olha (Problems of Friction and Wear, 2025)
The article classifies and discusses methods for calculating and improving gas-lubricated bearings. The classification takes into account the nature of the loads, the design, the method of generating lifting force, and the characteristics of the bearings. It is shown that the methods for calculating and designing gas-lubricated bearings in a drive are based on the joint iterative solution of a series of problems, the classical theory of motion stability by A.M. Lyapunov, and the solution of the generalized unsteady Reynolds equation. It has been determined that the main directions for improving (modernizing) contactless drives are the use of aerostatic bearings with conical bearings surfaces of various geometries (length, cone angle), ensuring the adjustability of stiffness and load-bearing capacity, natural frequencies of conical aerostatic bearings by changing the value of their average clearance with gas lubricant, comprehensive provision of dynamic stability of the contactless drive by adjusting the stiffness of conical aerostatic bearings in conjunction with adjusting the parameters of supercharging and throttling of lubricant, design changes in the distribution of masses and external loads, etc.